Effects of oral semaglutide on cardiovascular outcomes in individuals with type 2 diabetes and established atherosclerotic cardiovascular disease and/or chronic kidney disease: Design and baseline characteristics of SOUL, a randomized trial - McGuire, Darren K.; Busui, Rodica P.; Deanfield, John; Inzucchi, Silvio E.; Mann, Johannes F.E.; Marx, Nikolaus; Mulvagh, Sharon L.; Poulter, Neil; Engelmann, Mads D.M.; Hovingh, G. Kees; Ripa, Maria Sejersten; Gislum, Mette; et al. (Diabetes Obesity & Metabolism, 2023)
Aim: To describe the design of the SOUL trial (Semaglutide cardiOvascular oUtcomes triaL) and the baseline clinical data of its participants. Materials and methods: In SOUL, the effects of oral semaglutide, the first oral glucagon-like peptide-1 receptor agonist, on the risk of cardiovascular (CV) events in individuals with type 2 diabetes and established atherosclerotic CV disease (ASCVD) and/or chronic kidney disease (CKD) will be assessed. SOUL is a randomized, double-blind, parallel-group, placebo-controlled CV outcomes trial comparing oral semaglutide (14 mg once daily) with placebo, both in addition to standard of care, in individuals aged ≥50 years with type 2 diabetes and evidence of ASCVD (coronary artery disease [CAD], cerebrovascular disease, symptomatic peripheral arterial disease [PAD]) and/or CKD (estimated glomerular filtration rate <60 mL/min/1.73 m2). The primary outcome is time from randomization to first occurrence of a major adverse CV event (MACE; a composite of CV death, nonfatal myocardial infarction or nonfatal stroke). This event-driven trial will continue until 1225 first adjudication-confirmed MACEs have occurred. Enrolment has been completed. Results: Overall, 9650 participants were enrolled between June 17, 2019 and March 24, 2021 (men 71.1%, White ethnicity 68.9%, mean age 66.1 years, diabetes duration 15.4 years, body mass index 31.1 kg/m2, glycated haemoglobin 63.5 mmol/mol [8.0%]). The most frequently used antihyperglycaemic medications at baseline were metformin (75.7%), insulin and insulin analogues (50.5%), sulphonylureas (29.1%), sodium-glucose cotransporter-2 inhibitors (26.7%) and dipeptidyl peptidase-4 inhibitors (23.0%). At randomization, 70.7% of participants had CAD, 42.3% had CKD, 21.1% had cerebrovascular disease and 15.7% had symptomatic PAD (categories not mutually exclusive). Prevalent heart failure was reported in 23.0% of participants. Conclusion: SOUL will provide evidence regarding the CV effects of oral semaglutide in individuals with type 2 diabetes and established ASCVD and/or CKD.
CRIS-Team Scopus Importer:2023-04-28
Keywords: cardiovascular disease; GLP-1; randomized trial; semaglutide; type 2 diabetes